An Effort to Improve Students’ Activeness at Structure Class Using Slido App: Upaya Meningkatkan Keaktifan Siswa di Kelas Struktur Menggunakan Aplikasi Slide - Muthmainnah, Nur (JEES (Journal of English Educators Society), 2019)
This research was conducted to improve students’ activeness at structure class by sharing their idea, comment, questions and structure mastery. This research applied slido.com application as the media to teach. It was a classroom action research which had been conducted in two cycles. The subjects of this research were the third semester students of English Education Department of IAIN Salatiga. The writer took one of 3 classes as the sample of the research randomly. The researcher observed the improvement of students’ activeness at structure class by collecting the data through observation and measurement technique. The data were in the form of observation checklist and field notes, documentation, and students’ task. The data which were collected were analyzed to know the description of the class activity and the learning progress. After the cycles conducted, it resulted that there ware improvement in students’ activeness in delivering questions, giving comments, and doing simple task. The description of result was also proven with the students’ mean score improved from 51 in their pre-test into 67 in the second cycle. It can be drawn a conclusion that there is an improvement in students’ activeness in the structure class taught using slido application.